The Role of Family for Under-aged Working Children: (Case study: Child Busker on Balong Cangkring Crossroads Mojokerto) - Iik Ariyanti; Budi Harianto (Jurnal Perempuan dan Anak, 2024)
This study aims to explain the role of the family in child labor that occurs at the Balong Cangkring intersection in Mojokerto, seeing the phenomenon of child labor as a public concern for the weakening of human resources in the future era for the next generation. It is necessary to re-reflect the awareness of the role of parents that this child labor system becomes a capitalist system as the growth of family economic capital. This research method uses a qualitative case study analysis approach, the data collection methods used are interviews, observation and documentation. The results of the study show that child labor as buskers, car glass cleaners, hawkers that occur at the Balong Cangring intersection is influenced by an environment far from civilization, human resources and education which are difficult for children to access due to the weakening role of parents. The lack of the role of parents towards children and the pattern of sustenance that is not optimal so that child labor still occurs in Mojokerto. Human capitalism against child labor in Balong Cangkring is carried out by parents to earn money by employing underage children at school age.